Dry Chemical Process To Magnetize Pyrite And Ash For Removal From Coal - James K. Kindig (Society for Mining, Metallurgy & Exploration, 1976)
Hazen Research, Inc., has developed a new process for removing pyritic sulfur and ash from coal. Feed coal is contacted with iron carbonyl vapors, Fe(CO)5, at 190°C which puts a thin skin of magnetic material on the pyrite and ash, but does not affect the coal. Thus, low intensity magnetic separators yield a nonmagnetic coal, low in sulfur and ash, and a magnetic refuse, high in sulfur and ash. Results are given for clean coal produced by this method. A comparison is made between results of the magnetic process and the U. S. Bureau of Mines two-stage flotation process cleaning identical samples of Pittsburgh Coal. Capital and operating costs of the two cleaning methods are discussed.